Living with sickle cell in Uganda: A comprehensive perspective on challenges, coping strategies, and health interventions - Obeagu, Emmanuel Ifeanyi; Obeagu, Getrude Uzoma (Lippincott Williams & Wilkins, 2024)
Sickle cell anemia (SCA) is a hereditary blood disorder with profound implications for affected individuals, particularly in resource-limited settings such as Uganda. This review explores the multifaceted aspects of SCA in Uganda, focusing on epidemiology, challenges faced by individuals, coping strategies, healthcare disparities, and community support. The study incorporates a thorough examination of the genetic landscape, prevalence, and the impact of SCA on the quality of life in Uganda. Coping strategies and resilience play a pivotal role in mitigating the impact of SCA on affected individuals. This review critically evaluates the various coping mechanisms employed by individuals in Uganda and the resilience demonstrated in the face of chronic illness. It explores the psychological, social, and cultural dimensions of coping and resilience, shedding light on adaptive strategies that contribute to improved quality of life. This article aims to contribute valuable insights into the specific challenges faced by individuals with SCA in Uganda, offering a foundation for targeted interventions, improved healthcare policies, and increased awareness within both the medical community and the broader society.Sickle cell anemia (SCA) is a hereditary blood disorder with profound implications for affected individuals, particularly in resource-limited settings such as Uganda. This review explores the multifaceted aspects of SCA in Uganda, focusing on epidemiology, challenges faced by individuals, coping strategies, healthcare disparities, and community support. The study incorporates a thorough examination of the genetic landscape, prevalence, and the impact of SCA on the quality of life in Uganda. Coping strategies and resilience play a pivotal role in mitigating the impact of SCA on affected individuals. This review critically evaluates the various coping mechanisms employed by individuals in Uganda and the resilience demonstrated in the face of chronic illness. It explores the psychological, social, and cultural dimensions of coping and resilience, shedding light on adaptive strategies that contribute to improved quality of life. This article aims to contribute valuable insights into the specific challenges faced by individuals with SCA in Uganda, offering a foundation for targeted interventions, improved healthcare policies, and increased awareness within both the medical community and the broader society. MEDLINE - Academic